Study of critical point method for mixing zones in rivers / Othman Mohd. Ahijar and Ibrahim Othman - Mohd. Ahijar, Othman; Othman, Ibrahim (1986)
This project presents a steady state mathematical modelling technique to predict far field concentration distribution of pollutant in mixing zone of river. The models are based on the stream tube concept developed by Yotsukura and Sayre, and are modified by Gowda to account for the reach dependency of pollutant decay rate, tranverse diffusion factor and channel hydraulic parameters. An expression for allowable effluent concentration of a pollutant is obtained in term of critical concentration of water quality criterion. A graphical procedure for determining the longitudinal boundary of a limited use zone is described and validated by field data concentration profile of dissolved oxygen. The application of the methodology is outlined in a step-by-step design procedure and illustrated by field data analysis for ammonia nitrogen from palm oil waste collected in shallow stream located in Kapar, Selangor. In general the models presented in this project are applicable to conservative and exponentially decay pollutants.